Árvaság és mártírium: A gyámoltalan özvegy mint a református egyház metaforája a 17–18. században - Fazakas, Gergely Tamás (Studia Litteraria, 2012)
I argue that widowhood (often called “orphanage” in early modern texts) was an important metaphor of the contemporary Hungarian Calvinist Church. Several prayers, prayer books, congregational songs, jeremiads and sermons represented the martyrdom of the Church (and of the Hungarian nation as well) as a “helpless widow”, and lamented in her name. This cultural and rhetoric pattern was created and prescribed for the communities by several early modern texts, and were based on scriptural quotations from the Old Testament. (For instance: “How doth the city sit solitary, that was full of people! how is she become as a widow! she that was great among the nations, and princess among the provinces, how is she become tributary!” Lamentations 1, 1) I examine this metaphor not only in late seventeenth century texts, but also in the eighteenth century, when authors could not write openly about the Calvinist Church because of the new and increased censorship of the Habsburgs and the Catholic settlers in Transylvania. The representational patterns of Calvinist women in the eighteenth century is explored in this study thorough the example of countess Kata Bethlen.